Aplikasi SIG (Sistem Informasi Geografis) untuk Evaluasi Sistem Jaringan Drainase di Sub DAS Lowokwaru Kota Malang - Azizah Rachmawati (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2010)
Sub Basin Lowokwaru has 5.40 km2 with 6.39 km of main river length. It remains part of BasinBango in Malang City. Drainage system in Sub Basin Lowokwaru takes benefit from carrier channelsourcing from Bendung Sengkaling and constitutes a secondary irrigation channel. Flood or inundationcases at Sub Basin Lowokwaru remain due to incapability of drainage system capacity to accommodaterainwater overflow. This evaluation of drainage system in this area requires rainfall data collected fromRain Fall Station of Lowokwaru, Dau and Pendem. Meanwhile, primary data involve direct rainmeasurement at research site by using alat ukur hujan biasa (AUHB). The gauge has been used to measurewater surface elevation in outlet. Channel geometric data seem observed from map and direct measurementat research site. Research method used considered flood debit analysis grouped into two parts, Rational Method and Observation Way. The application of Geographic Information System (GIS) may be useful toacknowledge topographic condition, overflow coefficient, land use order, macro drainage system, and toanalyze planned flood debit in this area.Results of analysis drainage capacity at Sub Basin Lowokwaru, not available at all drainagechannel that able to receive 5 years shuttle period flood debit, there are 14 channels from 40 to that cannotovercome that. Therefore, it need channel dimension change. Observation debit received from observationpoint at SLWK. A channel is 1.5611 m3/s, and calculation result by Rational Method, it is 1.338 m3/s. Forrain level data (R24) at Sub Basin Lowokwaru is 94,590 mm (2 years), 123.1076 mm (5 years), 137.2918 mm(10 years).